The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.22722
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chemical composition and evaluation of antioxidant, antibacterial and antifungal activities of ethanol extract from Bidens pilosa L.

Abstract: Bidens pilosa L. is a species of plant that grows wild. It is commonly found in abundance in the Mekong Delta region of Vietnam. This study aimed to investigate the chemical composition, in vitro and in vivo antioxidant activity, the antimicrobial activity against some aquatic pathogenic bacteria and antifungal activity against plant pathogenic bacteria of Bidens pilosa L. extract. The results showed that Bidens pilosa L. extract had good antioxidant capacity through all four test methods of DPPH, ABTS •+ , RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…6 This suggested that the efficiency of activity might depend on geography and nutrition. Besides, comparison with the extract of several plants collected in Kien Giang province, such as Combretum quadrangulare, 16 Bidens pilosa, 18 Artemisia vulgaris, Pouzolzia zeylanica, and Costus speciosus, 19 S. cambodianum displayed the best antioxidant efficiency in tested assays. Therefore, the result demonstrated that SCE exerted its potent antioxidant activity due to the presence of active compounds.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…6 This suggested that the efficiency of activity might depend on geography and nutrition. Besides, comparison with the extract of several plants collected in Kien Giang province, such as Combretum quadrangulare, 16 Bidens pilosa, 18 Artemisia vulgaris, Pouzolzia zeylanica, and Costus speciosus, 19 S. cambodianum displayed the best antioxidant efficiency in tested assays. Therefore, the result demonstrated that SCE exerted its potent antioxidant activity due to the presence of active compounds.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…Several reports about in vivo antioxidant activity of some plant extracts, such as Bidens pilosa L., Combretum quadrangulare on Drosophila melanogaster fly model, showed that under the same conditions of oxidative stress, with the addition of these plant extracts, the mean life of the flies will be faster than that of the flies supplemented with the extract of S. cambodianum. 16,18…”
Section: In Vivo Antioxidant Activitymentioning
confidence: 99%
“…The literature also highlights the World Health Organization’s emphasis on using natural substances instead of antibiotics derived from nature. [ 12 13 ] The pharmaceutical sector will then produce these substances to create natural antimicrobials with minimal adverse effects. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Hence, developing a novel antibacterial agents that has a dual function of preventing the process of drug resistance and improving the properties of antimicrobial textiles against infectious disease are highly essential. From different literature survey, the emphasis of World Health Organization on the replacing antibiotics with natural ingredients was noticed (Son et al, 2022). The organization instructs the researchers to use rich reservoirs of useful compounds from nature to replace chemical and synthetic antibacterial agents (Bulut et al, 2021).…”
Section: Introductionmentioning
confidence: 99%